A Worldwide Examination of Exchange Market Quality: Greater Integrity Increases Market Efficiency - Aitken, Michael J. (Journal of business ethics, 2015)
We develop a framework for assessing security market quality (MQ), relating five elements of market design to three metrics of market integrity and two metrics of market efficiency. We empirically implement this integrity–efficiency MQ framework by testing a hypothesis that trade-based ramping manipulation at the close (MTC) raises execution costs on 24 security markets worldwide. Estimating a simultaneous equations model of ramping incidence, spreads, and the probability of deploying real-time surveillance (RTS), we show that quoted bid-ask spreads are positively related to the incidence of MTC across seven liquidity deciles. The magnitude is economically significant; improving market integrity by cutting MTC in half reduces spreads 6–11 %. Allowing direct market access in conjunction with RTS, conducting auctions at the close, and developing regulations that require surveillance, all reduce MTC and thereby lower spreads, assuring better market integrity and enhancing market efficiency. Introducing circuit breakers or prohibiting shorts poses integrity–efficiency tradeoffs.